2014
DOI: 10.7783/kjmcs.2014.22.4.276
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Polysaccharides Modulating Intestinal Immune System and Single Oral Dose Toxicity Test in Astragalus membranaceus Abovegroud Parts

Abstract: : The six polysaccharide fractions were prepared by chromatographic procedure from the hot water extracts of the aboveground parts of Astragalus membranaceus. These six polysaccharides from aboveground parts of Astragalus membranaceus Bunge were tested for gut-mucosal immune activity and acute toxicity. In a view of molecular weight, the six fractions were estimated to be 75000, 88000, 129000 and 345000 Da, respectively. Component sugar analysis indicated that these fractions were mainly consisted of galactose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Firstly, the presence of neutral residues of Ara f units was not necessary, as demonstrated by a retained bioactivity of WCP-Ib. Choi et al considered that the intestinal immune system-modulating activity of the aerial parts from Astragalus membranaceus was induced by a polygalacturonan moiety with neutral sugars such as arabinose and galactose [18], and Diallo et al showed a reduced complement fixing activity after the removal of terminal Ara f [19]. Le Normand also found a RG-I domain polymer ramified with highly-branched arabinans from spruce bark with immunomodulating activities [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, the presence of neutral residues of Ara f units was not necessary, as demonstrated by a retained bioactivity of WCP-Ib. Choi et al considered that the intestinal immune system-modulating activity of the aerial parts from Astragalus membranaceus was induced by a polygalacturonan moiety with neutral sugars such as arabinose and galactose [18], and Diallo et al showed a reduced complement fixing activity after the removal of terminal Ara f [19]. Le Normand also found a RG-I domain polymer ramified with highly-branched arabinans from spruce bark with immunomodulating activities [20].…”
Section: Discussionmentioning
confidence: 99%
“…Combining all results in vitro and the secretion of cytokines, it was demonstrated that WCP-Ia generally displayed a more effective immunoregulation function than WCP-I. Thus, we speculated if this was rooted in the Peyer’s patches, whose cytokine production could be enhanced by various natural polysaccharides, with most in a dose-dependent manner such as from Hordeum vulgare L. [23], Astragalus membranaceus [18], Entada africana [19], and Saccharum officinarum [22]. It could also account for the binding reaction on carbohydrate recognition domain (CRD), such as the modified pectin with polygalacturonic acid and RG-I regions that cleaved and de-esterified the HG backbone [24].…”
Section: Discussionmentioning
confidence: 99%